A NEW RECORD OF THE RHEOPHYTIC FERN Osmunda angustifolia (OSMUNDACEAE) FROM SUMATRA INCLUDING A NEW CYTOLOGICAL RECORD - Praptosuwiryo, Titien Ngatinem (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2015)
Osmunda angustifolia Ching ex Ching et Wang (Osmundaceae) was, formerly, known to be distributed in China (Guandong), Hainan, Hongkong, and Taiwan. Now, O. angustifolia is reported as a newly recorded species in Sumatra. A complete morphological description with photographs is presented. It is defined as a rare species in Indonesia. A cytological record is also reported for the first time for the Sumatran species. The somatic chromosome number of root tip cells of O. angustifolia is 2n = 44 (diploid).